Qualified majority voting and flexible integration for a more effective CFSP? A critical examination of the EU's options - Annegret Bendiek; Ronja Kempin; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2018)
The idea of qualified majority voting in the Common Foreign and Security Policy (CFSP) is not new, but its momentum has been boosted by the growing international challenges facing the EU. The German government argues that abolishing the unanimity principle would make the EU a stronger foreign policy actor in face of rising transatlantic tensions, a resurgent Russia and an expansive China. But short of an overall treaty amendment the legal possibilities are limited. Qualified majority voting in the CFSP is also problematic if it weakens the EU's internal legitimacy and external credibility. A dual approach is necessary: in the medium term strengthening the CFSP through flexible integration; in the long term supporting the development of a shared strategic culture through the establishment of collective European threat analysis and intelligence.
Keywords: 320